Os jogos digitais como qualificadores de aprendizagem de frações - Boszko, Leandro (2018)
The present work brings in its content the narrative and the discussion of the application of an educational product in the form of didactic sequencing, directed to the teaching of fractions, under the light of the semiotic representation theory of Reymond Duval added to the historical-cultural theory of Vygotsky. It was based on the understanding that the student can interpret different forms of representation of the same number, and this can be enhanced with the use of digital games, so widespread in the current modus vivendi. In this context, this dissertation is inserted in the line of research “Information, communication and interaction technologies applied to Science and Mathematics teaching”. The didactic sequence was replicated in an eighth grade class of an indigenous elementary school. Commonly, the topic covered in this didactic sequence is worked in sixth-grade classes, but because of an ethniccultural issue, the normal sequence of programmaticcontent becomes fragile. Another factor that must be considered is the lack of contact of these students with Information and Communication Technologies. However, it should be noted that there was an easy assimilation of these when presented to them. As a result, we can affirm that this work contributed significantly to the process of learning the contents of fractions, identifying in what way this sequence contributed to the process of teaching and learning concepts r elated to this content, especially the part-whole and its equivalences, and can be used as a pedagogical didactic resource by the professionals of education when working with these concepts. Finally, it is emphasized that this dissertation is accompanied by an educational product that gathers the material used in the meetings and the didactic sequence developed, which is available on the EduCapes portal, at the address <http://educapes.capes.gov.br/handle/capes/206989>.